Efficient Removal of 2,4-DCP by Nano Zero-Valent Iron-Reduced Graphene Oxide: Statistical Modeling and Process Optimization Using RSM-BBD Approach - Qi Jing; Shuo Qiao; Wenyu Xiao; Le Tong; Zhongyu Ren (Adsorption Science & Technology)
In this study, nano zero-valent iron-reduced graphene oxide (NZVI-rGO) composites were synthesized to remove 2,4-dichlorophenol (2,4-DCP) as an efficient adsorbent. Scanning electron microscopy (SEM) and X-ray diffraction (XRD) indicated that NZVI particles were successfully loaded and dispersed uniformly on rGO nanosheets. Fourier transform infrared spectroscopy (FTIR) analysis showed that the interaction between NZVI-rGO and 2,4-DCP promoted the adsorption process. A three-level, four-factor Box-Behnken design (BBD) of the response surface methodology (RSM) was used to optimize the influencing factors including NZVI-rGO dosage, 2,4-DCP initial concentration, reaction time and initial pH. A statistically significant, well-fitting quadratic regression model was successfully constructed to predict 2,4-DCP removal rate. The high F value (15.95), very low P value (<0.0001), nonsignificant lack of fit, and appropriate coefficient of determination (R2=0.941) demonstrate a good correlation between the experimental and predicted values of the proposed model. The analyses of variance reveal that NZVI-rGO dosage and reaction time have a positive effect on 2,4-DCP removal, whereas the increase of contaminant concentration and initial pH inhibit the removal, whereas the effect of contaminant concentration and initial pH is in reverse, where the change of NZVI-rGO dosage has the greatest effect. The optimum condition is1.215 g/L of NZVI-rGO dosage, 20.856 mg/L of 2,4-DCP concentration, 4.115 of pH, and 8.157 min of reaction time. It is verified by parallel experiments under the optimum condition, achieving the removal efficiency of100%.